Learning Motivation Factors in Terms of the Role of Parents of Mentally Retarded Students at SLBS Sunan Muria - Siska Siaka Ernia; Nur Fajrie Nur Fajrie; Diana Ermawati Diana Ermawati (Journal of Education and Culture (JEC), 2021)
This study aims to determine the factors that affect learning motivation during the Covid-19 pandemic in terms of the participation of parents of mentally retarded students at SLBS Sunan Muria Kudus. This study used a qualitative approach with the type of case study research at SLBS Sunan Muria. The research subjects were 5 mentally retarded students, 5 parents and 1 class teacher. This case study research uses data collection techniques in the form of observation, interviews, and documentation. Data analysis used the interactive model analysis techniques of Miles and Huberman (data reduction, data presentation, and conclusion drawing). The validity test uses the triangulation technique. Motivation to learn is the overall driving force both from within and from outside the student. Learning motivation factors are divided into two, namely internal factors and external factors. The results of this study indicate that the factors that influence children's learning are more on the encouragement factor of learning enthusiasm given by parents to children